Support for foreign ownership and integration in Eastern Europe: economic interests, ideological commitments, and democratic context - Rohrs Chneider, Robert; Whitefield, Stephen (2004)
Western models of popular support for economic integration usually stress costs and benefits. This article suggests that one cannot ignore the predominance of socialist-economic values in East-Central Europe. Consequently, it is argued and supported that (a) individual-level support for foreign ownership is best explained by ideological commitments to market ideas; (b) publics in more economically liberal countries more strongly support the idea of foreign ownership; and (c) citizens who reside in democratic countries, which experience greater controversy over foreign ownership, are less likely to accept the idea of foreign ownership just as they have a more negative image of the European Union. Theoretically, the study documents the limited applicability to Eastern Europe of Western-based models. Practically, it helps explain opposition to foreign ownership and, more generally, increasing controversy over the EU in first wave accession states. - Reproduced.
Keywords: European Union